THE USE OF ENGLISH MOVIES ON IMPROVING STUDENTS’ INTEREST IN LEARNING ENGLISH AT SMP NEGERI 2 NGUNUT - Anis Azimah (Universitas Islam Balitar, 2017)
In language learning, technology is an attractive media to the students, along with the development of the information technology, teacher should build up the learning process to be more interesting. Learning language successfully depends on many factors. One of the factors is interest of the learners themselves. Interest is an attitude favorably disposing and motivating one toward some objects, situations or idea. It relates to the activity which makes the learners to be involved in language learning process. In teaching English, teacher should conduct some techniques communicatively to build students ’ interest in learning process. Films are closed related to students ’ life. Younger likes watching movies or films. So, teacher can use films as the media in teaching English. It also can attract students to have high participation during learning process. Watching English movies can also be used as a technique to improve students ’ interest. It is not only improving students ’ interest, but also improving their achievement. Keywords : English Movie, Learning Interest. Â Received: 6 February, 2017; Accepter: 15 March, 2017